A method for preparing heavy metal adsorption material from black talc and heavy metal adsorption material

By simplifying the process, mix black slippery powder with low -concentration acid immersion, extract magnesium ions, and add three -valent metal salt or composition to the hybrid solution of magnesium ions to adjust the Malbi and PH values ​​to prepare excellent excellent excellence. The heavy metal adsorption material of adsorption performance solves the problem of complex process and poor adsorption effect in existing technologies.

CN117504813BActive Publication Date: 2025-01-24ZHONGNAN (SHANGRAO) METALLURGICAL IND RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311595010.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-01-24
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

In the prior art, the process of using black talc to prepare adsorbent materials is complex and the adsorption effect of prepared adsorbent materials is poor.

Method used

By mixing black talc powder with low-concentration acid leaching solution, heating and stirring, filtering, extracting magnesium ions, and then adding trivalent metal salts or combinations thereof to the mixed solution of magnesium ions, adjusting calcium, magnesium and trivalent metal salts. The molar ratio of metals is used to form a metal mixed solution, and the pH value is adjusted by dropping alkaline solution. Finally, the adsorbent material is obtained by standing for aging, filtration, washing and drying.

Benefits of technology

The process flow is simplified, the adsorption performance of the adsorption material is improved, and it has excellent heavy metal adsorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117504813B_ABST
    Figure CN117504813B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing heavy metal adsorption materials from black talc and the heavy metal adsorption materials, the method comprising: mixing black talc powder and an acid leaching solution of a first preset concentration according to a preset solid-liquid ratio to prepare a slurry, heating and stirring in a water bath at a first preset temperature, and filtering to obtain a mixed solution; adding a trivalent metal salt or a trivalent metal salt and a calcium salt to the mixed solution to obtain a metal mixed solution, and making the molar ratio of calcium and trivalent metal aluminum ions in the metal mixed solution a first preset ratio; dropping an alkaline solution of a second preset concentration into the metal mixed solution, adjusting the pH value in the metal mixed solution, and standing for aging; filtering the metal mixed solution after standing for aging to obtain a solid, then washing the solid with ionized water for a preset number of times, and drying at a second preset temperature for a third preset time to obtain an adsorption material. The present invention solves the problem in the prior art that the process for preparing adsorption materials using black talc is complicated and the adsorption effect of the prepared adsorption materials is poor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diversified utilization of black talc, and in particular to a method for preparing a heavy metal adsorption material from black talc and the heavy metal adsorption material. Background Art

[0002] Heavy metal pollution is a common type of wastewater pollution. After being ingested by the human body, heavy metals can cause various diseases such as kidney and liver damage. Currently, the most noteworthy ones are mercury, cadmium, chromium, etc. When heavy metals are discharged with wastewater, even if the concentration is very small, they may cause pollution due to enrichment. At present, the main methods for removing heavy metal ions from water bodies include precipitation, adsorption, ion exchange, membrane separation, electrolysis, etc. Adsorption is a method of making heavy metal ions adhere to the active site surface of the adsorbent through physical or chemical methods, thereby achieving the purpose of removing heavy metal ions. Adsorption has the advantages of fast reaction process speed and high adsorption efficiency, and is widely used in the removal of heavy metal impurities in wastewater.

[0003] Black talc is a general term for black and gray-black talc. The organic matter contained in it is the main reason for its black color. The main mineral in black talc is talc, and its content is more than 92%. Guangfeng black talc is a high-grade talc ore. Its main chemical components are silicon dioxide (about 65% to 69%) and magnesium oxide (about 26% to 28%), as well as a small amount of potassium, calcium, iron, sodium, etc. At present, the application of black talc is limited to low-end application industries such as raw materials for ceramics, rubber products, plastic products, coatings, papermaking fillers, and raw materials for waterproof materials. The stock of black talc is high, but the resource utilization rate is low, and the added value and market demand are also low, and its value has not been fully realized. The magnesium resources in black fossils can be used to prepare adsorption materials for removing heavy metal pollution.

[0004] In the prior art, although there are methods for extracting magnesium from black talc, these methods all use acid leaching to separate magnesium, and use multiple acids or high-concentration acids to achieve the leaching effect. The overall process is complicated and there is no effective utilization of magnesium. In addition, there are also methods for effectively utilizing magnesium components, but the method for preparing heavy metal adsorption materials from black talc has high reaction conditions, time-consuming processes, and poor adsorption effects of the prepared adsorption materials. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a method for preparing heavy metal adsorption materials using black talc and adsorption materials, so as to solve the problem that the process for preparing adsorption materials using black talc in the prior art is complicated and the adsorption effect of the prepared adsorption materials is poor.

[0006] The present invention provides a method for preparing a heavy metal adsorption material from black talc, characterized in that the method comprises the following steps:

[0007] The black talc powder and the acid leaching liquid of the first preset concentration are mixed at a preset solid-liquid ratio to prepare a slurry, heated in a water bath at a first preset temperature, stirred at a preset speed for a first preset time, and then filtered to obtain a mixed solution;

[0008] Adding a trivalent metal salt or a composition consisting of a trivalent metal salt and a calcium salt into the mixed solution to obtain a metal mixed solution, and making the molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal mixed solution be a first preset ratio, wherein the anions of the trivalent metal salt and the calcium salt are consistent with the anions of the acid leaching solution;

[0009] Adding a second preset concentration of alkaline solution to the metal mixed solution until the pH value of the metal mixed solution reaches a preset range, and then allowing the solution to stand for a second preset time;

[0010] The metal mixed solution after static aging is filtered to obtain a solid, and then the solid is washed with ionized water for a preset number of times, and dried at a second preset temperature for a third preset time to obtain an adsorption material.

[0011] The method for preparing heavy metal adsorption material from black talc in the present invention is to mix black talc powder with acid leaching solution in a certain proportion and stir, heat and filter, so that a certain amount of magnesium in black talc can be extracted in the form of ions, and then a certain amount of trivalent metal salt or a composition composed of trivalent metal salt and calcium salt is added to the mixed solution containing magnesium ions to adjust the molar ratio of calcium, magnesium and trivalent metal in the mixed solution to form a metal mixed solution, and the pH value in the metal mixed solution is adjusted by dropping an alkaline solution, and the solution is allowed to stand for aging, filtered after aging, and washed and dried to obtain an adsorption material, wherein since the adsorption material is prepared by black talc, a sufficient amount of magnesium can be extracted from the black talc by a single acid at a low concentration for preparing the adsorption material, without the need to completely extract magnesium from the black talc, thereby greatly simplifying the process flow, and in addition, the adsorption performance of the adsorption material is adjusted by adjusting the molar ratio of trivalent metal, calcium and magnesium, so that the adsorption material has excellent adsorption performance. Therefore, the present invention solves the problem that the process of preparing adsorption material using black talc in the prior art is complicated and the adsorption effect of the prepared adsorption material is poor.

[0012] In a possible design, the acid leaching solution is any one of sulfuric acid, hydrochloric acid, nitric acid, sulfurous acid, hydrofluoric acid and aqua regia.

[0013] In a possible design, the trivalent metal salt is an aluminum salt or an iron salt, and the anion of the trivalent metal salt is consistent with the anion of the acid leaching solution.

[0014] In a possible design, the molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal solution is 1-10:1-10:1-4.

[0015] In a possible design, the steps of mixing black talc powder and an acid leaching solution of a preset concentration at a preset solid-liquid ratio to prepare a slurry, heating the slurry in a water bath at a first preset temperature, stirring the slurry at a preset speed for a first preset time, and filtering the slurry to obtain a mixed solution include:

[0016] The black talc powder and the acid leaching solution with a concentration of 6% to 10% are mixed at a solid-liquid ratio of 1:5-10 to prepare a slurry, which is then heated in a water bath at 60°C-90°C and stirred at a speed of 100r / min-500r / min for 1h-4h. The slurry is then taken out of the water bath, naturally cooled to room temperature, and filtered to obtain a mixed solution.

[0017] In a possible design, the alkaline solution is any one of sodium hydroxide, potassium hydroxide, lithium hydroxide and calcium hydroxide.

[0018] In a possible design, the step of adding a second preset concentration of alkaline solution to the metal mixed solution until the pH value of the metal mixed solution reaches a preset range, and then standing and aging for a second preset time includes:

[0019] Add an alkaline solution with a concentration of 2mol / L-10mol / L to the metal mixed solution until the pH value of the metal mixed solution is between 10-12, and then let it stand for 0.5h-6h.

[0020] In a possible design, the steps of filtering the metal mixed solution after static aging to obtain a solid, washing the solid with ionized water for a preset number of times, and drying at a second preset temperature for a third preset time to obtain an adsorption material include:

[0021] The solid is washed with ionized water for 1-3 times, and the washed solid is dried at 70° C.-90° C. for 20 h-36 h to obtain an adsorption material.

[0022] In a possible design, the step of mixing the black talc powder and the acid leaching solution of the first preset concentration at a preset solid-liquid ratio to prepare a slurry, heating in a water bath at a first preset temperature, stirring at a preset speed for a first preset time, and filtering to obtain a mixed solution also includes:

[0023] The black talc is ground and passed through a 100-200 mesh sieve to obtain black talc powder.

[0024] In addition, another aspect of the present invention is to provide a heavy metal adsorption material, wherein the heavy metal adsorption material is prepared by the method for preparing a heavy metal adsorption material from black talc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1A flow chart of a method for preparing a heavy metal adsorption material from black talc provided in an embodiment of the present invention;

[0026] The following specific implementation manner will further illustrate the present invention in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0028] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0030] See also Figure 1 , which shows a method for preparing dust-free lithium hydroxide monohydrate provided by the present invention, the method comprising steps S10-S13:

[0031] Step S10, mixing the black talc powder and the acid leaching solution of the first preset concentration according to a preset solid-liquid ratio to prepare a slurry, heating the slurry in a water bath at a first preset temperature, stirring the slurry at a preset speed for a first preset time, and filtering the slurry to obtain a mixed solution.

[0032] Specifically, black talc powder and an acid leaching solution with a concentration of 6% to 10% are mixed at a solid-liquid ratio of 1:5-10 to prepare a slurry, which is then heated in a water bath at 60°C-90°C, and stirred at a speed of 100r / min-500r / min for 1h-4h, then taken out of the water bath, naturally cooled to room temperature, and filtered to obtain a mixed solution. Since the magnesium in the black talc is leached out by the acid leaching solution for the preparation of the adsorption material, rather than completely extracting the magnesium from the black talc to better separate silicon and magnesium, only a single type of acid with a lower concentration is required. Therefore, compared with the leaching process of multiple types of high-concentration acids, it is simpler, and the amount of acid used is less, saving costs.

[0033] In addition, the acid leaching liquid is any one of sulfuric acid, hydrochloric acid, nitric acid, sulfurous acid, hydrofluoric acid and aqua regia. Using different acids has a certain influence on the adsorption performance of the prepared adsorbent material. For example, the adsorption performance of the adsorbent material prepared by nitric acid is better than that of the adsorbent material prepared by hydrochloric acid, and the adsorption performance of the adsorbent material prepared by hydrochloric acid is better than that of the adsorbent material prepared by sulfuric acid. However, different types of acids have different requirements for reaction vessels in industrial applications. Therefore, considering the economy and the adsorption performance of the prepared adsorbent material, it is preferred to use hydrochloric acid to prepare the adsorbent material.

[0034] In addition, the concentration of the acid leaching solution is 6%-10%, for example, it can be 6%, 7%, 8%, 9% or 10%, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The solid-liquid ratio of black talc powder to the acid leaching solution is 1:5-10, for example, it can be 1:5, 1:6, 1:6.5, 1:7, 1:7.3, 1:8, 1:8.6, 1:9, 1:9.4 or 1:10, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The heating temperature of the slurry in the water bath is 60°C-90°C, for example, it can be 60°C, 65°C, 70°C, 73°C, 80°C, 84°C or 90°C, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The speed of stirring the slurry in the water bath is 100 r / min-500 r / min, for example, it can be 100 r / min, 120 r / min, 160 r / min, 200 r / min, 240 r / min, 280 r / min, 300 r / min, 350 r / min, 400 r / min, 470 r / min or 500 r / min, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The time for stirring the slurry in the water bath is 1 h-4 h, for example, it can be 1 h, 1.3 h, 1.6 h, 2 h, 2.4 h, 2.8 h, 3 h, 3.3 h, 3.7 h or 4 h, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0035] Step S11, adding a trivalent metal salt or a composition consisting of a trivalent metal salt and a calcium salt into the mixed solution to obtain a metal mixed solution, and making the molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal mixed solution a first preset ratio, wherein the anions of the trivalent metal salt and the calcium salt are consistent with the anions of the acid leaching solution.

[0036] Specifically, the molar ratio of trivalent metal ions, aluminum ions and calcium ions in the solution is adjusted by adding a trivalent metal salt or a composition of a trivalent metal salt and a calcium salt, so as to adjust the adsorption performance of the prepared adsorbent material, so that the adsorbent material has excellent adsorption performance. Since a certain amount of calcium already exists in black talc, when the ratio of calcium ions to magnesium ions in the solution is appropriate, only trivalent metal ions need to be added for adjustment, without adding calcium salt.

[0037] In addition, the trivalent metal salt is an aluminum salt or an iron salt, and the anion of the trivalent metal salt is consistent with the anion of the acid leaching solution. The material made by mixing divalent metals and trivalent metals and adding alkali and aging has a double-layer structure and good adsorption performance and can be used as an adsorption material. In addition, aluminum salts and iron salts in trivalent metal salts are common industrial salts and are more economical. Other trivalent metal salts can also be used, but the economic applicability is not high.

[0038] In addition, the molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal solution is 1-10:1-10:1-4, for example, it can be 1:1:1, 2:1:1, 3:3:2, 5:5:2, 5:5:4, 8:10:4, 10:9:4 or 7:8:3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Step S12, adding a second preset concentration of alkaline solution to the metal mixed solution until the pH value of the metal mixed solution reaches a preset range, and then standing and aging for a second preset time;

[0040] Specifically, an alkaline solution with a concentration of 2 mol / L-10 mol / L is added dropwise to the metal mixed solution until the pH value of the metal mixed solution is between 10 and 12, and then the solution is allowed to stand for 0.5 h to 6 h. The pH value of the metal mixed solution is accurately adjusted by adding the alkaline solution dropwise so that the pH value reaches between 10 and 12. In addition, the divalent metal and trivalent metal salts form a double-layer structure adsorption material with the alkali.

[0041] In addition, the alkaline solution is any one of sodium hydroxide, potassium hydroxide, lithium hydroxide and calcium hydroxide. Since potassium and lithium are relatively expensive, the use of calcium hydroxide will affect the ratio of divalent metal and trivalent metal ions in the solution, affecting the adsorption performance of the adsorbent material. Therefore, sodium hydroxide is preferably used.

[0042] In addition, the concentration of alkaline solution is 2mol / L-10mol / L, for example, it can be 2mol / L, 4mol / L, 5mol / L, 7mol / L, 9mol / L or 10mol / L, but it is not limited to the numerical value listed, and other unlisted numerical values ​​in the numerical range are equally applicable. The pH value in the metal mixed solution after dropping alkaline solution is 10-12, for example, it can be 10, 10.3, 10.5, 11, 11.6, 11.7 or 12, but it is not limited to the numerical value listed, and other unlisted numerical values ​​in the numerical range are equally applicable. The time of standing and aging is 0.5h-6h, for example, it can be 0.5h, 0.8h, 1h, 1.7h, 2h, 2.6h, 3h, 3.8h, 4h, 4.2h, 5h, 5.6h or 6h, but it is not limited to the numerical value listed, and other unlisted numerical values ​​in the numerical range are equally applicable.

[0043] Step S13, filtering the metal mixed solution after static aging to obtain a solid, then washing the solid with ionized water for a preset number of times, and drying at a second preset temperature for a third preset time to obtain an adsorption material.

[0044] Specifically, the solid is washed with ionized water for 1-3 times, and the washed solid is dried at 70°C-90°C for 20h-36h to obtain the adsorption material. The mixed solution still attached to the surface of the solid is rinsed clean with ionized water to prevent the substances in the mixed solution from solidifying and adhering to the adsorption material during subsequent drying, thereby affecting the adsorption performance of the adsorption material. In addition, the best number of washings with ionized water is 1 to 3 times, and the number of rinses can also be greater than 3 times, but the effect will not be better and water resources will be wasted. After washing, the solid is dried at different temperatures, and the drying time is changed accordingly. The lower the temperature, the longer the drying time, and the higher the temperature, the shorter the drying time.

[0045] In addition, black talcum powder is obtained by grinding black talcum powder and screening through a sieve of 100 mesh-200 mesh. By using black talcum powder for acid leaching, the reaction area can be increased to accelerate the reaction speed. In addition, the mesh number of the sieve can be 100 mesh, 120 mesh, 140 mesh, 180 mesh or 200 mesh, but is not limited to the numerical values ​​listed, and other unlisted numerical values ​​in the numerical range are also applicable. The larger the mesh size, the finer the black talcum powder, the faster the reaction speed, but the grinding time required is also longer.

[0046] In summary, the method for preparing heavy metal adsorption material from black talc in the present invention is to mix black talc powder with acid leaching solution in a certain proportion and stir, heat and filter, so that a certain amount of magnesium in black talc can be extracted in the form of ions, and then a certain amount of trivalent metal salt or a composition composed of trivalent metal salt and calcium salt is added to the mixed solution containing magnesium ions to adjust the molar ratio of calcium, magnesium and trivalent metal in the mixed solution to form a metal mixed solution, and the pH value in the metal mixed solution is adjusted by dropping an alkaline solution, and the solution is allowed to stand for aging, filtered after aging, and washed and dried to obtain an adsorption material, wherein since the adsorption material is prepared by black talc, a low concentration of a single acid can be used to extract a sufficient amount of magnesium from black talc for the preparation of the adsorption material, without the need to completely extract magnesium from the black talc, thereby greatly simplifying the process flow, and in addition, the adsorption performance of the adsorption material is adjusted by adjusting the molar ratio of trivalent metal, calcium and magnesium, so that the adsorption material has excellent adsorption performance. Therefore, the present invention solves the problem that the process for preparing adsorption materials using black talc in the prior art is complicated and the adsorption effect of the prepared adsorption material is poor.

[0047] Another aspect of the present invention is to provide a heavy metal adsorption material, which is prepared by the method for preparing the heavy metal adsorption material using black talc.

[0048] The present invention is further described below with specific embodiments:

[0049] Embodiment 1

[0050] Embodiment 1 of the present invention provides a method for preparing a heavy metal adsorption material from black talc, comprising the following steps:

[0051] Step 1: weigh 60 g of black talc powder passed through a 100-mesh sieve, add 300 ml of 2 mol / L hydrochloric acid, stir and react at 300 r / min in a 80°C water bath for 4 h, take out, cool and filter to obtain a mixed solution;

[0052] Step 2: Take 200 ml of the mixed solution, add calcium chloride and aluminum chloride to prepare a mixed metal solution with a molar ratio of calcium, magnesium and aluminum of 3:3:2;

[0053] Step 3: Under magnetic stirring at room temperature, add 2 mol / L NaOH solution dropwise to a final pH of 12, and allow to stand for 30 minutes;

[0054] Step 4: The solid obtained by filtration is washed three times with deionized water. After washing, the solid is dried at 80° C. for 24 hours to obtain an adsorption material.

[0055] In the specific implementation, the adsorption material was prepared according to the process flow and process parameters of the above embodiment 1, and then 0.1g of the adsorption material prepared in the above embodiment 1 was weighed into a conical flask, and 100ml of lead and cadmium solutions with concentrations of 100mg / L-500mg / L were added respectively. The flask was sealed and placed in a constant temperature oscillator for adsorption reaction. After adsorption for 3h, samples were taken to detect the lead and cadmium concentrations. The results are shown in Table 1:

[0056] Table 1

[0057]

[0058] It can be seen from Table 1 that with the increase of the concentration of heavy metal solution, the adsorption amount of heavy metals in the heavy metal solution by the adsorption material increases. However, if the concentration of the heavy metal solution is too high, the adsorption removal rate of the adsorption material will decrease. With the increase of the heavy metal concentration, the adsorption material reaches adsorption saturation, and finally the adsorption capacity of lead and cadmium reaches 456.3 mg / g and 498.55 mg / g, respectively.

[0059] Embodiment 2

[0060] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which differs from the first embodiment in that calcium chloride and aluminum chloride are added to prepare a mixed metal solution with a molar ratio of calcium, magnesium and aluminum of 1:1:1.

[0061] Embodiment 3

[0062] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which differs from the first embodiment in that calcium chloride and aluminum chloride are added to prepare a mixed metal solution with a molar ratio of calcium, magnesium and aluminum of 5:5:2.

[0063] Embodiment 4

[0064] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which is different from the second embodiment in that the acid leaching solution added is sulfuric acid, and the salts added are calcium sulfate and aluminum sulfate.

[0065] Embodiment 5

[0066] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which is different from the second embodiment in that the acid leaching solution added is iodine acid, and the salts added are calcium iodide and aluminum iodide.

[0067] Embodiment 6

[0068] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which differs from the second embodiment in that calcium chloride and ferric chloride are added to prepare a mixed metal solution with a molar ratio of calcium, iron and aluminum of 1:1:1.

[0069] Embodiment 7

[0070] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which is different from the sixth embodiment in that the acid leaching solution added is sulfuric acid, and the salts added are calcium sulfate and ferric sulfate.

[0071] Embodiment 8

[0072] This embodiment also provides a method for preparing a heavy metal adsorption material from black talc, which is different from the sixth embodiment in that the acid leaching solution added is chlorinated acid, and the salts added are calcium chlorinated acid and iron chlorinated acid.

[0073] Comparative Example 1

[0074] The first comparative example of the present invention provides a heavy metal adsorption material commonly used in the prior art, and the heavy metal adsorption material is a CaAl-x material.

[0075] Comparative Example 2

[0076] The second comparative example of the present invention provides another heavy metal adsorption material commonly used in the prior art, and the heavy metal adsorption material is a MgAl-x material.

[0077] In the specific implementation, the adsorption material was prepared according to the process flow and process parameters defined in the above embodiments 1 to 3, and then 0.1 g of the adsorption material prepared in the above embodiments 1 to 3 and the adsorption material in Comparative Example 1 and Comparative Example 2 were weighed into a conical flask, and 100 ml of a lead and cadmium solution with a concentration of 100 mg / L-500 mg / L was added, respectively. The flask was sealed and placed in a constant temperature oscillator for adsorption reaction. After 3 hours of adsorption, samples were taken to detect the lead and cadmium concentrations. The results are shown in Table 2:

[0078] Table 2

[0079]

[0080]

[0081] In the specific implementation, the adsorption material was prepared according to the process flow and process parameters defined in the above embodiments 2, 4 and 5, respectively. Then, 0.1 g of the adsorption material prepared in the above embodiments 2, 4 and 5 and the adsorption material in Comparative Examples 1 and 2 were weighed into a conical flask, and 100 ml of a lead and cadmium solution with a concentration of 100 mg / L-500 mg / L was added respectively. The flask was sealed and placed in a constant temperature oscillator for adsorption reaction. After 3 hours of adsorption, samples were taken to detect the lead and cadmium concentrations. The results are shown in Table 3:

[0082] Table 3

[0083]

[0084] In the specific implementation, the adsorption material is prepared according to the process flow and process parameters defined in the above embodiments 2, 6, 7 and 8, respectively. Then, 0.1 g of the adsorption material prepared in the above embodiments 2, 6, 7 and 8 and the adsorption material in Comparative Examples 1 and 2 are weighed in a conical flask, and 100 ml of a lead and cadmium solution with a concentration of 100 mg / L-500 mg / L is added respectively. The flask is sealed and placed in a constant temperature oscillator for adsorption reaction. After adsorption for 3 hours, samples are taken to detect the lead and cadmium concentrations. The results are shown in Table 4:

[0085] Table 4

[0086]

[0087] It can be seen from Table 2 that the different molar ratios of divalent metals and trivalent metals in the adsorbent material have an important influence on the adsorption performance of the adsorbent material for different metals. In these embodiments, the molar ratio of calcium, magnesium and aluminum is 5:5:2, which has a better removal rate for lead and cadmium, reaching more than 99%, while the removal rate of lead and cadmium by the existing materials in the comparative examples is less than 99%. It can be seen from Table 3 that the adsorbent materials prepared by different acid leaching solutions have different adsorption effects, among which the adsorbent material prepared by nitric acid has the highest removal efficiency for lead and cadmium. It can be seen from Table 4 that different trivalent metal salts have a greater influence on the adsorption performance of the prepared adsorbent material, and the adsorption effect of the adsorbent material prepared by iron salt is worse than that of the adsorbent material prepared by aluminum salt. Therefore, the adsorption performance of the adsorbent material can be adjusted by adjusting the type of acid leaching solution, the composition of the trivalent metal salt and the molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal solution, so that the adsorption performance of the adsorbent material is excellent.

[0088] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0089] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing heavy metal adsorption material from black talc, characterized in that: The method comprises: The black talc powder and the acid leaching liquid of the first preset concentration are mixed at a preset solid-liquid ratio to prepare a slurry, heated in a water bath at a first preset temperature, stirred at a preset speed for a first preset time, and then filtered to obtain a mixed solution; Adding a trivalent metal salt or a composition consisting of a trivalent metal salt and a calcium salt into the mixed solution to obtain a metal mixed solution, and making the molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal mixed solution be a first preset ratio, wherein the anions of the trivalent metal salt and the calcium salt are consistent with the anions of the acid leaching solution; Adding a second preset concentration of alkaline solution to the metal mixed solution until the pH value of the metal mixed solution reaches a preset range, and then allowing the solution to stand for a second preset time; Filtering the metal mixed solution after standing and aging to obtain a solid, then washing the solid with ionized water for a preset number of times, and drying at a second preset temperature for a third preset time to obtain an adsorption material; The steps of mixing black talc powder and acid leaching liquid of preset concentration at a preset solid-liquid ratio to prepare slurry, heating in a water bath at a first preset temperature, stirring at a preset speed for a first preset time, and filtering to obtain a mixed solution include: The black talc powder and the acid leaching solution with a concentration of 6% to 9% are mixed at a solid-liquid ratio of 1:5-10 to prepare a slurry, heated in a water bath at 60°C-90°C, and stirred at a speed of 100r / min-500r / min for 1h-4h, then taken out from the water bath, naturally cooled to room temperature, and filtered to obtain a mixed solution; The molar ratio of calcium ions, trivalent metal ions and aluminum ions in the metal solution is 5:5:2-4; The step of adding a second preset concentration of alkaline solution to the metal mixed solution until the pH value of the metal mixed solution reaches a preset range, and then standing and aging for a second preset time comprises: Add an alkaline solution with a concentration of 2 mol / L-10 mol / L to the metal mixed solution until the pH value of the metal mixed solution is between 10 and 12, and then allow to stand for 0.5 h to 6 h; The steps of filtering the metal mixed solution after standing and aging to obtain a solid, washing the solid with ionized water for a preset number of times, and drying at a second preset temperature for a third preset time to obtain an adsorption material include: The solid is washed with ionized water for 1-3 times, and the washed solid is dried at 70° C.-90° C. for 20 h-36 h to obtain an adsorption material.

2. The method for preparing heavy metal adsorption material from black talc according to claim 1, characterized in that: The acid leaching solution is any one of sulfuric acid, hydrochloric acid, nitric acid, sulfurous acid, hydrofluoric acid and aqua regia.

3. The method for preparing heavy metal adsorption material from black talc according to claim 1, characterized in that: The trivalent metal salt is an aluminum salt or an iron salt, and the anion of the trivalent metal salt is consistent with the anion of the acid leaching solution.

4. The method for preparing heavy metal adsorption material from black talc according to claim 1, characterized in that: The alkaline solution is any one of sodium hydroxide, potassium hydroxide, lithium hydroxide and calcium hydroxide.

5. The method for preparing heavy metal adsorption material from black talc according to claim 1, characterized in that: Before the step of mixing the black talc powder and the acid leaching liquid of the first preset concentration at a preset solid-liquid ratio to prepare a slurry, heating in a water bath at a first preset temperature, stirring at a preset speed for a first preset time, and filtering to obtain a mixed solution, the step further includes: The black talc is ground and passed through a 100-200 mesh sieve to obtain black talc powder.

6. A heavy metal adsorption material, characterized in that: The heavy metal adsorption material is prepared by the method for preparing heavy metal adsorption material from black talc according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for preparing calcium-magnesium-aluminum hydrotalcite by utilizing phosphate tailings

    CN111217385A

  • Magnesium-containing silica gel composite material as well as preparation method and application thereof

    CN112934168A